PENGARUH GORENGAN DAN INTENSITAS PENGGORENGAN TERHADAP KUALITAS MINYAK GORENG (Jurnal Pilar Sains, 2007)
Have been conducted research nfluenced type of fried and frying intensity to quality of cookingoil. This research aim to to know which type is which quickest destroy cooking oil and howmultiply frying be weared according to health standard. Parameter cooking oil quality hadstudied acidic number, iod number and peroxide number. Varies fried studied was tahu, tempeand banana. From research obtained, on third frying all off varies fried, cooking oil wasdemage.Key Word: Kualitas minyak goreng, gorengan, intensitas penggorengan